2013
DOI: 10.1089/apc.2012.0441
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and Outcomes of HIV Status Disclosure in HIV-Positive Young Women with Abuse Histories

Abstract: Young women with HIV and histories of physical and/or sexual abuse in childhood may be vulnerable to difficulties with disclosure to sexual partners. Abuse in childhood is highly prevalent in HIV-positive women, and has been associated with poorer communication, low assertiveness, low self worth, and increased risk for sexual and other risk behaviors that increase the risk of secondary transmission of HIV. HIV disclosure may be an important link between abuse and sexual risk behaviors. Qualitative interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…In this study, it was shown that participants would disclose this sensitive information to confidants that they relied on, trusted, and were close to. This finding was consistent with other studies from the US [ 10 , 21 ] that noted participants selected targets they trusted and were close to.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, it was shown that participants would disclose this sensitive information to confidants that they relied on, trusted, and were close to. This finding was consistent with other studies from the US [ 10 , 21 ] that noted participants selected targets they trusted and were close to.…”
Section: Discussionsupporting
confidence: 92%
“…[28][29][30][31] The presence of HIV infection may increase the risk of subsequent IPV within a relationship. 32,33 Identifying HIV patients, who have suffered or are suffering from the effects of IPV, offers the potential for mitigating its negative effects on both their general as well as HIV health.…”
Section: Introductionmentioning
confidence: 99%
“…Most theories, such as disease progression theory, emphasize the processes and motivations of the behavior based on beliefs about the costs and benefits associated with disclosure. [16][17][18] Accordingly, disclosure decisions are postulated to occur most often when HIV has advanced to symptomatic AIDS, making it challenging to hide one's illness. 19,20 However, empirical research has not demonstrated consistent associations between disease stage and disclosure to sexual partners.…”
Section: Introductionmentioning
confidence: 99%